Cultural Diversity Responsive Education: Exploration of Concepts and Dimensions - Dhungana, Jiwan (Education and Development, 2021)
This study has explored the concepts and dimensions of CDRE to understand its educational implications. The article is based on the review of conceptual and theoretical literature about cultural diversity and multicultural education following diversity-related issues. Guided by Vygotsky's sociocultural theory, post-modernism, and multicultural education theories, the study interprets the existing and observed educational status. By reviewing the policy documents including NCF, NASA, and SSDP and relevant research reports, the study found that the existing educational status of Nepal is being oriented towards particular social class or mainstream culture or teachers' culture. The paper has identified the dimensions of CDRE as CDRC, CDRI, R&I, and CDRA to ensure equity in education which can translate the existing particular social class or mainstream culture or teachers “culture-based instruction into a mass or all students” culture-based instruction in the classroom.